2022
DOI: 10.5607/en22012
|View full text |Cite
|
Sign up to set email alerts
|

The Three Musketeers in the Medial Prefrontal Cortex: Subregion-specific Structural and Functional Plasticity Underlying Fear Memory Stages

Abstract: Fear memory recruits various brain regions with long-lasting brain-wide subcellular events. The medial prefrontal cortex processes the emotional and cognitive functions required for adequately handling fear memory. Several studies have indicated that subdivisions within the medial prefrontal cortex, namely the prelimbic, infralimbic, and anterior cingulate cortices, may play different roles across fear memory states. Through a dedicated cytoarchitecture and connectivity, the three different regions of the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
3
1
0
Order By: Relevance
“…In contrast, because only the PLC is activated by recall of observational CFC memory in the demonstrator chamber at the remote timepoint, we speculate that upstream inputs to the PLC such as thalamus, entorhinal cortex, or a combination of different regions, which are activated during recall of direct CFC memory at the remote time point 21 , 52 , may trigger PLC neurons to elicit recall of observational CFC memory in the demonstrator chamber. Consistent with previous reports that demonstrate that the ILC is involved with extinction learning of fearful associations 84 86 , we found that the ILC was not activated in by recall of observational CFC memory in the observer or demonstrator chamber at either time point (Figs. 3f and 4g ).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, because only the PLC is activated by recall of observational CFC memory in the demonstrator chamber at the remote timepoint, we speculate that upstream inputs to the PLC such as thalamus, entorhinal cortex, or a combination of different regions, which are activated during recall of direct CFC memory at the remote time point 21 , 52 , may trigger PLC neurons to elicit recall of observational CFC memory in the demonstrator chamber. Consistent with previous reports that demonstrate that the ILC is involved with extinction learning of fearful associations 84 86 , we found that the ILC was not activated in by recall of observational CFC memory in the observer or demonstrator chamber at either time point (Figs. 3f and 4g ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that the aMPFC is a crucial brain area in depressive symptomatology and is involved in the underlying pathology of depression, 47 which could support our findings to some extent. Recent studies have shown that the aMPFC processes the emotional and cognitive functions required for adequately handling episodic and fear memory 48 . In our study, the E nod of the left aMPFC positively correlated with global cognition measured by MMSE in the MCID group, which is compatible with the role of the aMPFC in the development of cognitive impairments.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that the aMPFC processes the emotional and cognitive functions required for adequately handling episodic and fear memory. 48 In our study, the E nod of the left aMPFC positively correlated with global cognition measured by MMSE in the MCID group, which is compatible with the role of the aMPFC in the development of cognitive impairments. The findings suggested that the left aMPFC may serve as a biomarker of different clinical phenotypic presentations of MCI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation